Evaluation of the clinical characteristics and prognostic factors of gastrointestinal mucosa‐associated lymphoid tissue (MALT) lymphoma. Issue 9 (September 2014) - Xu, Xiaoxiao; Wang, Zhenxing; Yu, Yong; Wang, Yafei; Zhang, Lianyu; Sun, Baocun; Da, Wanming; Zhang, Yizhuo
Abstract Background and Aim This study was undertaken to evaluate the clinical characteristics, prognostic factors, and long‐term outcomes of patients with mucosa‐associated lymphoid tissue (MALT) lymphoma in the gastrointestinal (GI) tract. Methods Clinical and pathological features of patients with MALT lymphoma in the GI tract, who were treated consecutively at Tianjin Medical University Cancer Institute and Hospital from 2001 to 2011, were evaluated retrospectively. Results Among a total of 99 identified cases, 79.79% of lymphomas were localized in the stomach, 20.20% in the intestinal tract, and disseminated disease was detected in 35.4% of cases. The estimated 5‐year overall survival (OS) and 5‐year progression‐free survival (PFS) rates were 73.1% and 65.1%, respectively. The comparison between stomach and intestinal tract lymphomas demonstrated no significant difference in characteristics, but nodal involvement was significantly lower in gastric MALT lymphoma (26.6%) as compared with intestinal tract MALT lymphoma (60%, P = 0.006). The outcomes of gastric and intestinal MALT lymphomas were similar (OS, P = 0.492; PFS, P = 0.408), and so was the survival between proximal and distal gastric lymphomas (OS, P = 0.077; PFS, P = 0.181). Serum lactate dehydrogenase level above normal was identified as the only adverse prognostic factor for both OS and PFS. Conclusion The clinical characteristics and outcomes demonstrated no significant differences between gastric and intestinal tract MALT lymphomas. Serum lactate dehydrogenase level was an independent prognostic factor for the survival of GI MALT lymphoma.